Cooperative Learning Approach in Increasing Knowledge of First Aid for Bleeding - Elfi Rahmawati; Didik Susetiyanto Atmojo; Puguh Santoso (HealthCare Nursing Journal, 2023)
Bleeding that occurs due to trauma needs to be treated early to stop it as soon as possible. Trauma events often occur in the community so that it is hoped that there will be a positive contribution from students who are part of the community to provide first aid to victims who experience bleeding quickly and accurately. The purpose of this study was to determine the increase in knowledge of KSR team students on first aid for bleeding. This research was conducted at SMA Negeri 1 Kediri. The population in this study were members of the KSR who had never received the material and practice of first aid for bleeding before. This study uses a pre-experimental one group pre-post test design. Filling out the questionnaire was carried out before and after the intervention, respondents were given health education, discussions, and brief training on first aid in cases of bleeding in groups. This study used the Wilcoxon statistical test with a = 0.05. The variable in this study was knowledge of first aid on bleeding.